Peningkatan kesadaran kesehatan rongga mulut pada komunitas taman edukasi anak pemulung di Gampong Jawa, Banda Aceh [Increasing awareness of oral health in the scavengers educational park community in Jawa Village, Banda Aceh] - Ossa, Yuli Fatzia; Fitri, Maida; Sari, Maulidia Indah (Buletin Pengabdian, 2024)
Oral health can affect the overall health of the body, yet there are still many people who do not take care of their oral health. Many factors influence this, including lack of knowledge and cost constraints in maintaining oral health. This service aims to increase awareness of the importance of oral health in the Scavenger Children's Educational Park community. The method of the service is through counseling on the importance of maintaining oral health, teaching how to brush teeth, and conducting oral health screenings. From the oral cavity examination, 38 children were examined with the condition of deciduous teeth with cavities, namely 139 teeth. The number of permanent teeth with caries was 74. The caries index of permanent teeth obtained during the oral cavity examination of children in the age of 6-12 years in the educational park community is 1.73, and the caries index of milk teeth is 5.35. In conclusion, this service activity provided preliminary data on the oral health screening of the children of the Scavenger Children's Educational Park Community in Gampong Jawa. The high caries index in these children can be an input for health services, especially in Gampong Jawa, where children in the area deserve special attention.